Study on the GCL’s Response to Hydraulic Uplift - Budihardjo, Mochamad; Chegenizadeh, A; Nikraz, Hamid (Planetary Scientific Research Center, 2012)
Most of landfill sites in developed countries employ GCL as bottom liners to replace compacted clay liner. However, various water level and direction might be faced by GCL during its operation. These conditions can make the GLC to deform and decrease its hydraulic capability. In this experiment, the GCL was tested with two direction of water flow to see whether any deformation that causes the GCL to lose its hydraulic performance. The results showed that the hydraulic performance of the GCL was constant while facing a water flow coming from above even some area started to be slightly thinner than others. In contrast, the GCL started to uplift, curved and lost its hydraulic performance when thewater pressure coming from underneath. The bentonite particles also moved aside from higher hydraulic pressure zone into lower pressure area creating diverse thickness.